Faith as a strategy for fighting cancer - Nunes, Yara Martins (2024)
Spiritual beliefs can influence the way individuals cope with illness, with a positive impact on reducing physical and emotional symptoms. The aim of this study was to assess the influence of faith and spirituality as coping strategies for cancer. This was a descriptive cross-sectional study carried out in a public hospital in the Federal District. The sample consisted of 30 patients with various types of cancer undergoing chemotherapy. Data was collected through a semi-structured interview and the Religious-Spiritual Coping Scale (CRE Scale), the first CRE assessment tool in Brazil, based on the North American RCOPE scale by Pargament, Koenig and Perez (2000). There was a significant influence of religiosity/spirituality on coping with cancer and intensification of faith after being diagnosed with the disease. It was found that, after diagnosis, people seek out religiosity/spirituality more, reviewing values and transforming themselves to better cope with the illness